2009
DOI: 10.1111/j.1939-1676.2009.0322.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily Rhythms of Left Atrial Pressure in Beagle Dogs with Mitral Valve Regurgitation

Abstract: Background: Mitral valve regurgitation (MR) causes increased left atrial pressure (LAP) and is associated with occurrence of clinical signs. It will be useful to understand diurnal variations of LAP for the management of MR.Hypothesis: Circulatory parameters and diurnal rhythm are linked to clinical signs in cardiac diseases. LAP also exhibits a diurnal rhythm in dogs with MR.Animals: Five healthy Beagle dogs weighing 9.8-12.8 kg (3 males and 2 females; aged 2 years) were used. Methods: A radiotelemetry system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
(26 reference statements)
0
21
1
Order By: Relevance
“…10 Thoracic radiograph and echocardiograph examinations were performed for the presence of pulmonary edema and cardiac dilation. After the radio telemetry transmitter implantation, the dogs were rested for at least 5 weeks, until no major variations were identified on echocardiographic evaluation and LAP.…”
Section: Animalsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Thoracic radiograph and echocardiograph examinations were performed for the presence of pulmonary edema and cardiac dilation. After the radio telemetry transmitter implantation, the dogs were rested for at least 5 weeks, until no major variations were identified on echocardiographic evaluation and LAP.…”
Section: Animalsmentioning
confidence: 99%
“…We have previously reported the 24-hour LAP profiles of and the effect of angiotensin-converting enzyme (ACE) inhibitors on experimentally induced MR dogs with a radio telemetry system. 10,11 The previous study has demonstrated that this system is useful for the evaluation of hemodynamic changes that occur with the administration of furosemide.In the present study, we monitored the LAP of dogs with experimentary induced MR with a radio telemetry system and evaluated the effect of furosemide in different administration routes. Echocardiographic evaluations and blood pressure measurements were also conducted, and the effect of furosemide on MR was evaluated by analyzing of pathophysiological changes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been few study of the amlodipine in dogs with MR and amlodipine’s effect on LAP has not been fully evaluated in a quantitative manner because of difficulties in directly measuring LAP. We have previously used a radiotelemetry system to report the effects of angiotensin-converting enzyme (ACE) inhibitors and furosemide in dogs with experimentally-induced MR [14-16], and we believe this system would be useful for evaluation of hemodynamic changes after administration of amlodipine.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, all the records during the whole experimental period were also used to maintain the dogs' conditions. Preparation of MR model dogs and transmitter implantation: Surgical and postoperative care procedures were as described in the previous report [15]. Follow-up care included the auscultation of lung/cardiac sound and blood test (complete blood cell count, blood urea nitrogen, creatinine, alkaline phosphatase and electrolytes).…”
Section: Study 1 Constructing Regression Equations Between Lap and Ementioning
confidence: 99%